Solutions of acrylonitrile copolymers in N-methylmorpholine-N-oxide: Structure, properties, fiber spinning. (July 2017) - Kulichikhin, Valery; Golova, Lyudmila; Makarov, Igor; Bondarenko, Galina; Makarova, Veronika; Ilyin, Sergey; Skvortsov, Ivan; Berkovich, Anna
Graphical abstract: Highlights: First time the solutions of co-polyacrylonitrile in N-methylmorpholine-N-oxide are prepared. The dissolution mechanism is proposed. Properties of concentrated solutions are investigated. Fibers are spun and carbonized. Abstract: Highly concentrated solutions of acrylonitrile copolymers (PAN) in N -methylmorpholine N -oxide (NMMO) were obtained via the solid-phase activation method. Specific interactions in the system at different stages of the dissolution process starting from solid-state activation and finishing with a transition to a viscous state were studied by IR spectroscopy, polarizing microscopy, interferometry and rheology. It was shown that the crucial factor determining a possibility of dissolution is the complex formation between carboxyl groups in the copolymer and the electron-donor N → O group in the solvent. This complex arises during the process of solid-phase activation of PAN and crystalline NMMO, which thereafter melts and transforms into a homogeneous solution having viscoelastic behavior. In the temperature range of 130–135 °C, irreversible chemical transformations take place in the solutions due to the coherent interaction between nitrile groups; these reactions lead to the formation of cyclic structures and conjugated sequences in the PAN chains. Rheological properties follow this process via specific viscosity and viscoelasticity evolution in time.